PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA PADA BIDANG PANAS BUMI DI KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL - Lestari, Suci; Alexandra, Esther Tiara; Tobing, Erie Hotman H (Jurnal Manajemen & Bisnis Jayakarta, 2022)
This study aims to find out the obstacles and to find the strategies in capacity building of human resources in geothermal. This research uses quantitative research with descriptive approach. In this study, the method of data collection is documentation, the data used in the form of interviews. Data analysis carried out in this study was qualitative data analysis, where data analysis was carried out in a non-statistical way, namely research carried out by describing the data obtained in words or sentences and literature studies. The results of this study indicate that Indonesia still lacks human resources who have specific competencies to work in geothermal projects